The Association Between Smoking and Renal Function in People Over 20 Years Old - Fu, Yi-Cheng; Xu, Zhi-Liang; Zhao, Ming-Yi; Xu, Ke (Frontiers in Medicine, 2022)
There are many conclusions about renal function studies in direct smokers. To find out the possible relationship between smoking and renal function, we collected 10,267 people from the National Health and Nutrition Program Testing Survey (NHANES) over 20 years old from 2013 to 2018 to assess smoking exposure by serum cotinine. We estimated the glomerular filtration rate (eGFR) and used a multivariate linear regression models and smooth curve fittings to assess the relationship between smoking and renal function. We found an inverse relationship between serum cotinine and eGFR. In the subgroup analysis, a nonlinear relationship was found between serum cotinine and eGFR. In a subgroup analysis of sex, we found an inflection point between men and women regarding the relationship of serum cotinine and eGFR, where the inflection point was 183ng/mL and 465ng/mL, this is illustrated when in the >183ng/mL and <465ng/mL, male serum cotinine and eGFR may not be strictly proportional to them; similarly, between the inflection points 227ng/mL and 412ng/mL in women, eGFR changes were smaller with increasing serum cotinine concentrations. However, in the subgroup analysis of age, we could find that serum cotinine showed a clear negative correlation with eGFR in people aged 20-39 years, butin people over 40 years old, a weak correlation was shown. In a stratified analysis of ethnicity, we found that negative associations were significant in Mexican American and Other Hispanic, and a weaker ones in Non-Hispanic White and Non-Hispanic Black. Through the negative correlation between serum cotinine and eGFR, we can conclude that as the smoking quantity increases, smoking leads to a decrease in renal function, so that we can reduce the incidence of chronic kidney disease by advocating for smoking restriction. The results in the subgroup analysis tell us that in young people, by advocating smoking cessation early, we can very effectively prevent kidney disease in this population, and thus we can reduce the incidence of chronic kidney disease. Smoking should be included as an independent risk factor for chronic kidney disease.